Perspectivas político-eleitoral dos vereadores e fiéis assembleianos do Município de São Paulo: um estudo de caso nos Ministérios Jesus é a Fonte da Vida e Ipiranga - Silva, Fernando Pereira (2017)
In the year 2010 according to the IBGE, the capital of São Paulo had more than 10 million people and within that number, 1,240,660 people living in the capital who informed the same research agency in 2010 belonged to an evangelical church. In this sense, we note that for the municipal elections in São Paulo we obtained the candidacy of 30 evangelical names for the position of councilman in the city, from 1145 to 55 vacancies. At the end of the elections, only 12 were elected and received a total of 568,292 valid votes. In this way, the research here intends to present the political-electoral perspectives of the city councilmen and faithful congregations of the city of São Paulo, counting on field research, interview, semi-structured questionnaire, content and discursive analyzes of the data collected. Throughout the research, we observe how these perspectives are presented based on the answers and theories of Pierre Bourdieu and Max Weber as a matter of priority. At the end of the analysis we can see how these perspectives can tell a lot about the relation that these politicians and faithful have of the subject in question, considering that there is a double way when we speak of elections, where the positions can be as diverse as possible In an environment that there are dominant and dominated.